Published byRhoda Madison Green Modified over 8 years ago
Lesson 9.3 Factoring Trinomials: x² + bx + c
Objectives: To factor trinomials of the form x² + bx + c To solve equations of the form x²+ bx + c = 0
Factoring x² + bx + c (x + )(x + )
To factor a trinomial of the form x² + bx + c find two numbers with the sum of the middle term b and product of the last term c. Example: x² + 11x + 24 Factors of 24 Sum of 11 sum of 11 product of 24 (x + )(x + ) Note: X² will always factor into x and x
Ex. 1: Factor each trinomial.
x² + 7x + 12 2. x² - 12x + 27
3. x² + 3x - 18 4. x² - x - 20
a + a² 6. x² - 4xy + 3y²
Your turn…… p² - 2p – 35 h² + 3h - 40 c² - 3c + 2 c² + 12c + 35
Some equations of the form x² + bx + c = 0 can be solved by factoring and then using the Zero Product Property.
Ex. 2: Solve each equation.
1. x² + 16x + 28 = 0 2. y² + 4y – 12 = 0
3. z² = z 4. c² - 50 = -23c
Your turn… 5. x² + 2x = 15 6. 14p + p² = 51
SUMMARY To factor a trinomial of the form x² + bx + c
find two numbers with the sum of the middle term b and product of the last term c. To solve an equation of the form x² + bx + c = 0, set the equation equal to zero, factor, and use the Zero Product Property to solve. NBA #3, page 493, problems even
© 2023 SlidePlayer.com Inc.
All rights reserved.